2019
DOI: 10.1093/ofid/ofz371
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Penicillin Skin Testing on Aztreonam Stewardship and Cost Savings in Immunocompromised Cancer Patients

Abstract: Objective Reported penicillin allergies result in alternative antimicrobial use and are associated with worse outcomes and increased costs. Penicillin skin testing (PST) has recently been shown to be safe and effective in immunocompromised cancer patients, yet its impact on antimicrobial costs and aztreonam utilization has not been evaluated in this population. Method From September 2017 to January 2018, we screened all admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
8
2
Order By: Relevance
“…Optimized BLA status in transplant recipients remains a worthy antimicrobial stewardship goal as beta‐lactams are less toxic and costly than alternative antibiotics 10,30 . While our study did not find an association between reported BLA status and SSI incidence, it did demonstrate substantial antimicrobial utilization in transplant recipients in the first month following transplantion.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Optimized BLA status in transplant recipients remains a worthy antimicrobial stewardship goal as beta‐lactams are less toxic and costly than alternative antibiotics 10,30 . While our study did not find an association between reported BLA status and SSI incidence, it did demonstrate substantial antimicrobial utilization in transplant recipients in the first month following transplantion.…”
Section: Discussioncontrasting
confidence: 74%
“…17 Optimized BLA status in transplant recipients remains a worthy antimicrobial stewardship goal as beta-lactams are less toxic and costly than alternative antibiotics. 10,30 While our study did not find an association between reported BLA status and SSI incidence, it did demonstrate substantial antimicrobial utilization in transplant recipients in the first month following transplantion. SOT recipients experience a variety of complications postoperatively, and, as a result of chronic immunosuppression, this population is at a higher risk of infection and often receives more antimicrobials than the general population.…”
Section: Discussioncontrasting
confidence: 67%
“…Additionally, this study found a significant difference in antimicrobial cost savings following penicillin evaluations in this cancer cohort. 19 Efficacy of penicillin allergy evaluations has also been shown in transplant populations (see Table 2). One center performed a retrospective analysis of hematopoietic stem cell transplant recipients who underwent BLA evaluation (inpatient or outpatient ST followed by OC to amoxicillin) as part of their routine pretransplantation evaluation.…”
Section: Aal Evaluation In the Immunocompromised Hostmentioning
confidence: 99%
“…performed ST followed by OC to amoxicillin in a cohort of hospitalized cancer patients (67% solid tumor, 33% hematologic malignancy). Ninety‐four percent were delabeled (4% indeterminate skin test result, 2% delayed rash) 19 . Seventy‐two percent of the cohort was able to switch to beta‐lactam antibiotics post‐intervention, with a subsequent decrease in aztreonam use.…”
Section: Aal Evaluation In the Immunocompromised Hostmentioning
confidence: 99%
“…A decrease in aztreonam usage is associated with significant cost savings. 8 Removal of inappropriate penicillin allergy labels also facilitates an easier transition to oral antibiotics, a key component of antibiotic stewardship programs that can aid in more timely hospital discharge. 6,9 Although many factors contribute to a patient's length of stay, we did note a decreased median length of stay during the intervention period.…”
Section: Discussionmentioning
confidence: 99%